PEMANFAATAN Rhizoctonia MIKORIZA UNTUK PENGENDALIAN PENYAKIT BUSUK AKAR PADA TANAMAN ANGGREK Spathoglottis plica - , SOELISTIJONO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of this study were to provide S. plicata orchid resistance to root rot disease using mycorrhizal Rhizoctonia, and to look into the induced resistance mechanism on Spathoglottis plicata by mycorrhizal Rhizoctonia against root rot. Mycorrhizal Rhizoctonia and pathogenic Rhizoctonia sp. were isolated from Karanganyar, Magelang, and Sleman, and differentiated morphologically and molecularly. The observations on induced resistance included disease severity index, formation of the total phenolic compound, increased peroxidase activity, and lignification. The results showed that pathogenic Rhizoctonia sp. colonies were brownish white, cell size was 3.51 - 1.0 Âµm and consisted of 2 groups, which were binucleate (Twmg, Mgl, and Slmn 1) and multinucleate (Slmn 2). Multinucleate pathogenic Rhizoctonia isolates belong to Rhizoctonia solani (Slmn 2). All colonies of Rhizoctonia mycorrhiza (M1, M2, M3, and M4) were brownish white or light brown, cell size were 4.8 - 11.7 Âµm and binucleate. Mycorrhizal Rhizoctonia and pathogenic Rhizoctonia were not morphologically different, but genetically different. There were different characters between binucleate pathogenic and multinucleate Rhizoctonia. Genetic of the binucleate pathogenic Rhizoctonia were different from each other, and genetic of mycorrhizal Rhizoctonia were also different from each other. The association between mycorrhizal Rhizoctonia and S. plicata occurred when the plantlets were 4 months old as shown by the formation of peloton structure in the root cortex. Mycorrhizal Rhizoctonia was able to control root rot disease with induced resistance, which was shown by the reduction of the disease severity index. The disease severity index of induced orchid by mycorrhizal Rhizoctonia was 1.78, whereas the disease severity index of the non induced was 2.84, and that of the control plants only 0.15. The highest total phenolic compound on orchid induced by mycorrhiza Rhizoctonia was 36, ppm, whereas that of the non induced was 33.2 ppm, and that of the control plants was only 9.67 ppm. The increased total phenol compound was followed by an increased peroxidase activity. The peroxidase activity after inoculation with R. solani in induced orchid root was higher (0.375 minute/mg protein) than that non induced orchid roots (0.238 minute/mg protein). The peroxidase activity on non treated orchid root was undetected. The increased level in peroxidase activity indicated that the lignification had occurred. Orchid induced by mycorrhizal Rhizoctonia would be lignified in the root epidermal tissue, whereas non induced orchid was not lignified and badly damaged. Lignification did not occurred in the control plants.